Astonishing X-Men. Vol. 1, Gifted - Joss Whedon; John Cassaday; Marvel Comics Group (Marvel Comics, 2004)
The newly re-formed X-Men team, under the leadership Cyclops and Emma Frost, is ready to astonish the world, but breaking news about a cure for the mutant gene takes the wind out of their sails. Plus, they go to battle with the enigmatic Ord and receive some unexpected help.